LINGUACULTURAL FEATURES OF FOOD RELATED VOCABULARY IN ENGLISH AND UZBEK - Kamolova Rushana Ibodovna,; Yusupova Shoira Botirovna, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation:  This  article lights  up  the  linguacultural  features  of  food-related vocabulary in English and Uzbek languages. It explores how cultural values, traditions, and national identity are reflected in the naming, use, and perception of food items. The  study  is  grounded  in  linguoculturology  and  semantics,  focusing  on  culturally marked food terms, metaphors, and idiomatic expressions associated with food.